Mexico’s Place-Names and Road-Names as Psycholinguistic Evidence in the Search for Al Dorado - Lonergan, Julia Elizabeth (Signo, 2019)
The paper explores the socio-cultural practice of place naming and road naming, using Conceptual Metaphor Theory as a framework to deconstruct the ‘Place Names’ and ‘Road Names’ of two important Spanish Missions that were part of North Mexico’s main routes in Nueva Hispania: the Santa Maria Valenciana of the Port of Saint Antoinette of the Bear, West Texas Bexar, now partly in New Mexico, and the Mission San Xavier de Baca, in Tuboc, Southern Tucson, Arizona. Conceptual metaphor theory and linguistic anthropology are combined for the theoretical grounding and data acquisition methods, forming conceptual metaphor mappings for the framework for a modern-day search for Al’Dorado. Gibbs (1994) and Lakoff & Johnson, (1999) research provide the theoretical foundations for this search for “the Lost City of Gold”. The assumptions of the cognitive mechanism of language will require establishing the conceptual mappings between the abstract place names from the ‘Royal Road’, the Camino Real and the ‘Rio Grande River-Route’. The physical source domain is the geographical and historical structures along the Roads and Missions that connect the Baja (lower) and Nuevo (upper) Camino Real. The study moves across New Mexico and Arizona, as they connect with a Spanish Moorish Mission, called the La Jornada. The Stations on the Cross(ing) along the Horn of Plenty may contain the material culture artifacts to establish a physical source domain, where the historical Lost City of Gold an are more than abstract legends, but may have come from the traveling caravans from Vispania along the Royal Road. The paper focuses on the Sandbar of Doyle, where the Sultan of Zandibar Santo Tovar, (Duval, Doyle) built an ancient Al Medina, or Alameda, the ‘City in the Middle’. The Chico Tovar as the architect and builder of Las Cruces New Mexico. The word Al’ Dorado translates into a Proper Noun, ‘the Golden Boy’, -n. the adored; but it also translates as ‘the Golden (Dorar- the Hardened Dome) City’-n creating with allusion and ellipsis in the ambiguity of finding Al-Dorado. Gibbs, (1994) and Lakoff & Johnson, (1999) research on conceptual metaphor theory can be used to as a framework to explore the social cultural practice of naming, and continue the search for Al’ Dorado. Two main coherent relations will appear in the language linking the Proper Names and Place Name: Hermigues, or Alfonso Hermigues of the Santa Cruz de los Reyes, with those who became Ordenes de San Fernando y San Hermenegildo. This was Herman’s Guild, Hermileone, and they controlled the dispatches along the Camino Real with the ‘Armados de la Camino Real’ (‘The Armed of the Camino Real’) who were ‘military or nobility’ hiding as ‘clergy’. They became the conversos at the Fall of the Moors in Muslim Spain. The Black Berry Cabeza de Baca caravans give us the ‘Moro’ Spanish Moors and here is are allusions to the Color and Herald of Black Salazars of Xavior The Chico Tovar, whose name is also ‘Zaed Bivar’ in New Spain, now part of New Mexico and Arizona.